MR imaging in Crohn's disease: correlation of MR motility measurement with histopathology in the terminal ileum. Issue 9 (7th June 2013) - Cullmann, J. L.; Bickelhaupt, S.; Froehlich, J. M.; SZUCS‐FARKAS, Z.; Tutuian, R.; Patuto, N.; Dawson, H.; Patak, M. A.
Abstract Background The objective of the study was to correlate MR‐detectable motility alterations of the terminal ileum with biopsy‐documented active and chronic changes in Crohn's disease. Methods This IRB approved retrospective analysis of 43 patients included magnetic resonance enterography (MRE) and terminal ileum biopsies (<2 weeks apart). Motility was measured at the terminal ileum using coronal 2D trueFISP pulse sequences (1.5T MRI, TR 83.8, TE1.89) and dedicated motility assessment software. Motility grading (hypermotility, normal, hypomotility, complete arrest) was agreed by two experienced readers. Motility was compared and correlated with histopathology using two‐tailed Kruskal–Wallis test and paired Spearman Rank‐Order Correlation tests. Key Results Motility abnormalities were present in 27/43 patients: nine hypomotility and 18 complete arrest. Active disease was diagnosed on 15 biopsies: eight moderate and seven severe inflammatory activity. Chronic changes were diagnosed on 17 biopsies: 13 moderate and four severe cases. In four patients with normal motility alterations on histopathology were diagnosed. Histopathology correlated with presence (P = 0.0056 for hypomotility and P = 0.0119 for complete arrest) and grade (P < 0.0001; P = 0.0004) of motility alterations. A significant difference in the motility was observed in patients with active or chronic CD compared with patients without disease (P < 0.001; P = 0.0024). Conclusions & Inferences MR‐detectable motility changes of the terminal ileum correlate with histopathological findings both in active and chronic CD. Motility changes may indicate the presence pathology, but do not allow differentiation of active and chronic disease.